Ethics and business ethics, and the financial crisis. About axiology and business: history of slavery is like a circle / Ética, ética nos negócios e a crise financeira. Sobre axiologia e negócios: a história da escravidão como ciclo - Bunikowski, Dawid "Renas" (REVISTA QUAESTIO IURIS, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] --> Trabalho enviado em 08 de outubro de 2014. Aceito em 22 de janeiro de 2015. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] --><span style="font-size: 10.0pt; font-family: "Arno Pro Light Display","serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Arno Pro Light Display"; color: #333333; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">DOI: http://dx.doi.org/10.12957/rqi.2015.15355 Abstract The papers acquaints the readers with problems of ethics and business ethics in context of the financial crisis. The article is to underline a role of ethics in business. An ethical approach is incredibly important in the economy and the business activity. There is no good economy and market without axiology in social order. There is no economy and economic activities without much deeper foundations based on moral universal values such as honesty or transparency or dignity. We should go back to papal teaching and classics of moral philosophy. I believe that we can create the real axiology including such the values. The global financial crisis is rather an axiological crisis than strictly economic because the foundations and real reasons of the financial crisis have strictly moral character. Greed, profit, fraud, misinformation, new morality of homo economicus created the new world of consumers and the structurally and institutionally hermetic world of the markets and the corporations. It is a sad but more realistic view of the corporations and economy. History of slavery is like a circle: free people became stupid consumers; free people working in corporations became its cynical or ordinary slaves, the honest became the dishonest; free people became dishonest businessmen and businesswomen, without heart, mercy and reason. The system we live is rotten (politics, law, business, media, consumerism ideology), requiring changes. We should start with moral education to make ordinary people, the citizens, who create the commonwealth, really more responsible, competent and free in choices. Keywords: morality, ethics, business ethics, axiology, values, financial crisis, slavery, freedom, moral philosophy, law, social order, consumerism, rotten system <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] --> Resumo No presente artigo há a tentativa de familiarizar o leitor com problemas de ética e ética nos negócios, em um contexto de crise financeira. O artigo procura delinear o papel da ética como fator atuante no mundo dos negócios. Uma abordagem ética é extremamente importante na economia e na atividade empresarial. Não há economia ou atividade econômica louvável se não houver axiologia, um fim social. Não há economia e atividade econômica sem fundamentos muito mais profundos, com base em valores universais morais como honestidade ou transparência ou dignidade. Devemos voltar ao ensino papal e ao estudo da filosofia moral clássica. Eu acredito que nós podemos criar a axiologia real, incluindo esses valores. A crise financeira mundial é também uma crise axiológica e não estritamente econômica, porque os fundamentos e as razões reais da crise financeira tem caráter estritamente moral. A ganância, o lucro, a fraude, a desinformação e a nova moralidade do homo economicus criaram o novo mundo dos consumidores e do mundo estruturalmente e institucionalmente hermético dos mercados e das corporações. É uma visão triste, mas mais realista sobre as corporações e a economia. A história da escravidão é como um ciclo: o homem livre se tornou um consumidor estúpido; o trabalhador livre se tornou um escravo das corporações; o honesto se tornou desonesto; pessoas livres se tornaram desonestos homens e mulheres de negócios, sem coração, misericórdia ou razão. O sistema em que vivemos está podre (política, direito, economia, mídia, ideologia consumista), exigindo mudanças. Deviamos começar melhorando a educação moral, a fim de que o homem comum, o cidadão, aquele que cria a comunidade, torne-se de fato mais responsável, competente e livre em suas escolhas. Palavras-chave: moral, ética, ética nos negócios, axiologia, valores, crise financeira, escravidão, liberdade, filosofia moral, lei, ordem social, o consumismo, o sistema podre. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> Trabalho enviado em 08 de outubro de 2014. Aceito em 22 de janeiro de 2015. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->